Effects of Aging on Rat Pedicled Fasciocutaneous Flap Survival. (23rd August 2013) - Roy, Sudeep; Heffelfinger, Ryan; Hota, Salini; Duddy, Beth; Pribitkin, Edmund A.
Abstract : Objectives: Characterize the effects of aging on rat pedicled fasciocutaneous flap survival and associated ischemia‐induced vascular proliferation and inflammation. Methods: After approval from the Institutional Animal Care and Use Committees, three cohorts containing six young rats, six intermediate‐aged rats, and six old rats were created. A fasciocutaneous flap based axially on the inferior epigastric vessel was raised on each rat and rotated 60 degrees into a contralateral defect. Animals were sacrificed seven days postoperatively and flaps harvested. Each flap was evaluated for degree of gross necrosis, and samples were sent for both histopathological evaluation of vessel density as well as protein analysis for levels of vascular endothelial growth factor (VEGF), heme‐oxygenase 1 (HO‐1), and pyruvate dehydrogenase kinase (PDH‐K) to assess angiogenesis and cellular response to ischemic injury. Results: There was a clear and scaled distinction between the three groups (0% of the young rats, 33% of the intermediate rats, and 100% of the old rats) in terms of observable necrosis of the distal flap on gross examination. Histology showed decreased vascular density as well as increased fibrosis, apoptosis, and inflammation in specimens collected from the old rats compared to the younger groups, and this correlated with expected variations in VEGF, HO‐1, and PDH‐K levels. Conclusions: Age correlates inversely with flap survival, angiogenesis, and resistance to ischemic injury in this rat pedicled fasciocutaneous flap model. Accordingly, this flap model can be used to explore the effects of interventions designed to ameliorate the effects of aging on these variables.